2021
DOI: 10.1038/s41467-021-22599-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of protein trafficking by in vivo tissue-specific labeling

Abstract: Conventional approaches to identify secreted factors that regulate homeostasis are limited in their abilities to identify the tissues/cells of origin and destination. We established a platform to identify secreted protein trafficking between organs using an engineered biotin ligase (BirA*G3) that biotinylates, promiscuously, proteins in a subcellular compartment of one tissue. Subsequently, biotinylated proteins are affinity-enriched and identified from distal organs using quantitative mass spectrometry. Apply… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 99 publications
2
79
0
Order By: Relevance
“…Addition of a small molecule substrate to live cells results in catalytic generation of a reactive biotin species (such as biotin-phenoxyl radical for APEX or biotin-AMP for TurboID) from the active site of the promiscuous enzyme, which diffuses outward to covalently tag proximal endogenous proteins. PL methods have been used to map organelle proteomes (mitochondrion, ER, lipid droplets, stress granules) 6 , dynamic interactomes 7 , 8 , and in vivo secretomes 9 , 10 . Recently, PL was extended to spatial mapping of transcriptomes in living cells 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Addition of a small molecule substrate to live cells results in catalytic generation of a reactive biotin species (such as biotin-phenoxyl radical for APEX or biotin-AMP for TurboID) from the active site of the promiscuous enzyme, which diffuses outward to covalently tag proximal endogenous proteins. PL methods have been used to map organelle proteomes (mitochondrion, ER, lipid droplets, stress granules) 6 , dynamic interactomes 7 , 8 , and in vivo secretomes 9 , 10 . Recently, PL was extended to spatial mapping of transcriptomes in living cells 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 24 generated ER-BioID mice and characterized muscle-derived serum protein changes with exercise training. Droujinine et al 25 showed protein trafficking by tissue-specific labeling in Drosophila using BirA*G3 and identified serum proteins secreted from mouse teratomas. All these studies used the KDEL signal peptide to position TurboID, BioID, or BirA*G3 to the ER lumen whereas our study utilizes the membrane-anchored Sec61b-TurboID which is not subject to secretion.…”
Section: Resultsmentioning
confidence: 99%
“…In hopes of identifying new secreted biomarkers controlled by the VHL tumor suppressor gene, we introduced the BirA biotin ligase fused to an ER localization signal (ER-BirA 7,8 ), or the corresponding empty expression vector (EV), into 786-O human VHL -/- clear cell renal carcinoma cells (ccRCCs) that reexpress the VHL in the presence of Doxycycline (Dox) (Fig. 1a,b and Extended Data Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Here we show that histone H3 is horizontally transferred between viable cells. Using an ER-targeted biotin ligase to detect secreted proteins 7,8 , we serendipitously discovered that histone H3 is selectively secreted by autophagic cells relative to histones H2A, H2B, and H4. Specific H3 posttranslational modifications are enriched or depleted on secreted H3 relative to intracellular H3, suggesting that specific PTMs dictate H3’s ability to be secreted or the information it conveys to neighboring cells.…”
mentioning
confidence: 99%